2021
DOI: 10.3390/bs11100134
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Prevalence among Secondary School Children in Khamis Mushait City, Southwestern Saudi Arabia

Abstract: Bullying is a type of behavior that involves frequent, hostile activities expected to harm another person physically, mentally, or emotionally. Bullying behavior uses force, pressure, or threats to maltreat, forcefully dominate, or terrify another individual. The aim of this study was to assess the bullying prevalence and related features among secondary school pupils in Khamis Mushait city, southwestern Saudi Arabia. A cross-sectional investigation was performed among governmental and private secondary school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…After screening the articles for relevance, 14 articles that met the inclusion criteria were included in the present review. [6][7][8][18][19][20][21][22][23][24][25][26][27][28] The information pertaining to the study design and setting, objectives addressed, and all relevant findings including prevalence and type of violence are tabulated in Table 2. The studies highlighted that violence from a perpetrator and victim perspectives has preceding relevant factors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…After screening the articles for relevance, 14 articles that met the inclusion criteria were included in the present review. [6][7][8][18][19][20][21][22][23][24][25][26][27][28] The information pertaining to the study design and setting, objectives addressed, and all relevant findings including prevalence and type of violence are tabulated in Table 2. The studies highlighted that violence from a perpetrator and victim perspectives has preceding relevant factors (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of bullying, in general, among students, was 60.0%; there was a significant difference between males and females in the prevalence of bullying behavior, which was 67.9% and 51.6%, respectively (P 0.001) [13]. It seems that boys are globally more discourteous than girls, A study conducted by Alsaleem with his colleagues in Saudia Arabia in 2021 among 300 students of secondary school aged 15-18 years, they found that the overall bullying prevalence rate was 64.7% and males had two times more than female [20]. A study was conducted among 2724 students of classes 10th and 11th, this study found a highly significant smoking role in antisocial deviation in the different ethnic groups, for example, smoking vs cursing, lying, exhibiting one's boldness sex gender identity, or smoking, dangerously driving a motor vehicle; their study found that current smoking connected to antisocial behavior differed considerably between males and females [21].…”
Section: Discussionmentioning
confidence: 96%
“…The students' scores were calculated and divided into three levels using cutoff points for behavioral discourteous from 22-36 is respectful, 37-51 is mild disrespectful and 52-66 scores is a disrespectful student. Likewise, for the physically discourteous aspect as pacifist (15)(16)(17)(18)(19)(20)(21)(22)(23)(24), mercurial (25)(26)(27)(28)(29)(30)(31)(32)(33)(34), and hostile (35-45). In the same way, determining the verbal discourteous was from (7-11) which stands for polite, (12)(13)(14)(15)(16) for abusive, and (17-21) very offensive verbal behavior.…”
Section: Objectives Of the Studymentioning
confidence: 99%
“…Global literature reports high levels of bullying victimization among high school learners [ 4 , 5 , 6 ]. The prevalence varies across regions and countries and communities, and while a high prevalence of 74% was reported in Samoa [ 4 ], the average prevalence for the Sub Saharan Africa region countries was 38.8% [ 7 ].…”
Section: Introductionmentioning
confidence: 99%